Answer:

**Answer:**

**12.5%**

**Step-by-step explanation:**

125 is 12.5% of 1000

About 58 million people die every year. About how many die each day, on average?

2.Make up a new pair of numbers that would makethe same shade of green. Explain how you knowthey would make the same shade of green.

Which of the following expressions is equal to 5^6/ 5^2?1.) 5×5×52.) 1/5×5×5×53.) 5×5×5×54.) 3

Find the answer for 10 + 10

What does it mean to evaluate?

2.Make up a new pair of numbers that would makethe same shade of green. Explain how you knowthey would make the same shade of green.

Which of the following expressions is equal to 5^6/ 5^2?1.) 5×5×52.) 1/5×5×5×53.) 5×5×5×54.) 3

Find the answer for 10 + 10

What does it mean to evaluate?

**Answer:**

3x + 21

**Step-by-step explanation:**

(3)(x+7)

Now, we distribute the 3 in each term of (x+7)

So, 3*x = 3x and 3*7 = 21.

So our resulting term would be 3x+21.

What is the height of the tower (h)?

The **height **of the **tower **(h) is approximately 186.4 feet.

A **ratio **is simply the relation between two amounts showing how many times a value is contained within another value.

Given the data in the quesion;

- Aidan's height = 5.5ft
- length of Aidan's shadow = 9ft
- height of the tower = ?
- length of the tower's shadow = 305ft

We can set up a **proportion **to solve for the height of the tower:

Aidan's height / length of Aidan's shadow = height of the tower / length of the tower's shadow

Plugging in the values we know, we get:

5.5 / 9 = h / 305

To solve for h, we can cross-multiply and simplify:

9h = 5.5 × 305

9h = 1667.5

h = 1667.5 / 9

h = 186.4 ft

Therefore, the **value **of h is 186.4 feet.

Learn more about **ratio **here: brainly.com/question/30061012

#SPJ1

Answer:

Power analysis

Step-by-step explanation:

Power analysis is a significant part of test structure. It permits us to decide the example size required to recognize an impact of a given size with a given level of certainty. On the other hand, it permits us to decide the likelihood of recognizing an impact of a given size with a given degree of certainty, under example size requirements. On the off chance that the likelihood is unsuitably low, we would be shrewd to adjust or forsake the analysis.

The principle reason underlying power analysis is to assist the analyst with determining the littlest example size that is appropriate to recognize the impact of a given test at the ideal degree of hugeness.

6n - 3(2n - 5)

SHOW ALL WORK!

6n - 3(2n-5)

mutiply the bracket by -3

(-3)(2n)= -6n

(-3)(-5)= 15

6n-6n+15

0+15

answer:

15

6n-3(2n-5)

6n-(6n-15)

6n-6n+15

(6n-6n)+15

=15

6n-(6n-15)

6n-6n+15

(6n-6n)+15

=15

Answer: -7twice

Step-by-step explanation:

This is a question on root of quadratic equation. The interpretation of the question

x² 14x + 49 is

x² + 14x + 49 = 0.meaning that we are to find two possible values for x that will make the expression equal 0.

We can use any of the methods earlier taught. For the purpose of this class, I am using factorization methods

x² + 14x + 49 = 0

Now, find the product of the first and the last terms, is

x² × 49 = 49×²

Now find two terms such that their productbis 49x² and their sum equals 14x, the one in the middle.

We have several factors of 49x² but only one will give sum of 14x. Because of the time, I will only go straight to the required factors .

49x² = 7x × 7x and the sum gives 14x the middle terms..

Now we now replace the middle one by the factors and then factorize by grouping.

x² + 14x + 49 = 0

x² + 7x + 7x + 49 = 0

x(x + 7) + 7(x + 7) = 0

(x + 7)(x + 7). = 0

Now to find this value of x,

x + 7 = 0

x. = -7twice.

The root of the equation = -7twice.

**Answer:**

*7. g(3) = 42*

*8. f(6) = - 124*

*9. g(15) = 3*

*10. h(-3) = 1/8*

**Step-by-step explanation:**

**7.*** g(x) = 4x² + 6*

*g(3) = 4×3² + 6*

*= 4×9 + 6*

*= 36 + 6*

*= 42*

**8.*** f(x) = - 3x² - 4x + 8*

*f(6) = - 3×6² - 4×6 + 8*

*= - 3×36 - 24 + 8*

*= - 108 -16*

*= - 124*

**9. ***g(x) = √(x - 6)*

*g(15) = √(15 - 6)*

*= √9*

*= 3*

**10. ***h(x) = 2ˣ*

*h(-3) = 2⁻³*

*= 1/2³*

*= 1/8*